Structural, Microstructural, Electrical Properties of Lanthanum doped-Bismuth Titanate Ceramics Prepared by Low Temperature Combustion Synthesis - Azlan, Umar Al-Amani; Mohd Noor, Ahmad Fauzi (International Institute for the Science of Sintering, 2017)
In this work, lanthanum doped-bismuth titanate with different contents were successfully prepared by low-temperature combustion synthesis, and subsequently, sintered at 1000 oC for 3 hours. Their structural, microstructural and electrical were systematically studied. It was found that the structural distortion of orthorhombic structure tends to transforms to a tetragonal with the increase in La content.This change is most probably due to relaxations of orthorhombic distortion and octahedral tilting because of the difference in the ionic radius of Bi3+ and La3+. Upon increasing of La content, the grain size remarkable decreases resulted in uniform grain size with better relative density. Thus, the electrical properties of La doping were greatly improved in comparison to pure sample.